2001
DOI: 10.1080/00036840122890
|View full text |Cite
|
Sign up to set email alerts
|

Fixed investment and economic growth: new results on causality

Abstract: This study re-examines the issue of causality between investment shares and economic growth. A methodology is applied based on Arellano and Bond (1991), and Holtz-Eakin, Newey and Rosen (1988) to quinquennial panel data on growth and investment shares for the post war period and shows that, contrary to previous results in the literature, causality between fixed investment and growth runs in both directions. Investment shares Granger-cause growth rates and growth rates Granger-cause investment shares. Granger c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 16 publications
5
26
2
1
Order By: Relevance
“…As a result, examination of the causality between investment in ICT capital and economic growth emerges as a necessary and promising research undertaking. Podrecca and Carmeci (2001) examined causality between fixed investment shares and economic growth for the post-war period and suggested that contrary to the previous results in the literature, causality between the two variables runs in both directions. The empirical results are consistent with the predictions of Solow-type growth model, but they contrast with the classical view that fixed capital investment is the key to the long-run economic growth (Solow, 1956;1957).…”
Section: Evidence From Developed and Developing Countries 113contrasting
confidence: 49%
“…As a result, examination of the causality between investment in ICT capital and economic growth emerges as a necessary and promising research undertaking. Podrecca and Carmeci (2001) examined causality between fixed investment shares and economic growth for the post-war period and suggested that contrary to the previous results in the literature, causality between the two variables runs in both directions. The empirical results are consistent with the predictions of Solow-type growth model, but they contrast with the classical view that fixed capital investment is the key to the long-run economic growth (Solow, 1956;1957).…”
Section: Evidence From Developed and Developing Countries 113contrasting
confidence: 49%
“…Petrakos and Arvanitidis (1) summarize that investments are a key determinant of economic growth identified in neoclassical as well as endogenous growth model. The theory is supported by numerous scientific studies, including Kormendi and Meguire (2); Levine and Renelt (3); Mankiw (4), Auerbach et al (5); Barro and Sala-iMartin (6), Sala-i-Martin (7); Easterly (8); Podrecca u Carmeci (9). On the one hand, the scientific interest is attracted by the direct effects of increased cash flows to the local economies, respectively the impact on employment, incomes and domestic demand, while other studies focused on the "secondary" effects on the dynamics of domestic investment and the entry into and exit from the market of local businesses.…”
Section: Introductionmentioning
confidence: 89%
“…Higher wages for health workforces create more consumption and savings which contributes to economic growth. The investments stimulate positively to economic growth through technological diffusion (Podrecca and Carmeci, 2001;Schneider, 2005). The conceptual framework above summarizes that; health, education, labour skills and investment contribute positively to economic growth (as measured by GDP per capita).…”
Section: Theoretical Conceptual Frameworkmentioning
confidence: 99%